1971
DOI: 10.1099/0022-1317-13-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Smallpox Vaccine: Immunogenicity of Inactivated Intracellular and Extracellular Vaccinia Virus

Abstract: SUMMARYInactivated vaccines were prepared from cell-associated vaccinia virus liberated mechanically from sheep dermal pulp and cultures of infected chick cells and from naturally released 'free' or extracellular virus. The inactivated vaccines induced dermal immunity in rabbits and protected mice against intracerebral challenge. Antibody produced by rabbits in response to inactivated cell-associated virus neutralized cell-associated but not free virus. Antibody to inactivated 'free' virus neutralized neither,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 5 publications
2
53
0
Order By: Relevance
“…Obviously antibody to antigens such as lpc 1, 2 and 6 which are not surface components of intracellular virus can play no part in the neutralization of that virus. However, one or more of these antigens may represent the additional immunogenic component of extracellular virus described recently (Appleyard et al 1971;Turner & Squires, 1971). Extracellular forms of vaccinia and cowpox viruses were neutralized by absorbed antisera, indicating that the extracellular forms of all three viruses share an additional common antigen, or antigens.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Obviously antibody to antigens such as lpc 1, 2 and 6 which are not surface components of intracellular virus can play no part in the neutralization of that virus. However, one or more of these antigens may represent the additional immunogenic component of extracellular virus described recently (Appleyard et al 1971;Turner & Squires, 1971). Extracellular forms of vaccinia and cowpox viruses were neutralized by absorbed antisera, indicating that the extracellular forms of all three viruses share an additional common antigen, or antigens.…”
Section: Discussionmentioning
confidence: 91%
“…The immunological response to poxvirus infection and the role of antibody in recovery from infection have not been Poxvirus surface antigens considered. The immunological response to poxvirus infection has been studied extensively since Downie (1939a) showed that cowpox and vaccinia viruses were not identical, and the recent work of Boulter (Boulter, 1969;Appleyard et al 1971) and Turner & Squires (1971) suggests that antibody to extracellular virus may be more important than antibody to intracellular virus in recovery from infection. Nevertheless intracellular forms of poxvirus are neutralized by antisera, and it is from the study of intracellular virus that most of our knowledge of the serology and chemistry of poxviruses has been obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EEV is released from the cell and has an extra lipid envelope with 10 associated proteins which are absent from INV (Payne, 1978(Payne, , 1979. These proteins endow EEV with different biological and immunological properties (Boulter, 1969;Appleyard et al, 1971;Turner & Squires, 1971;Boulter & Appleyard, 1973). Despite its low abundance, EEV is important for the efficient dissemination of virus in vitro and in vivo (Appleyard et al, 1971 ;Boulter & Appleyard, 1973;Payne, 1980;Payne & Kristensson, 1985).…”
Section: Vaccinia Virus Biologymentioning
confidence: 99%